IMPLEMENTASI METODE DHARMA CARITA PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DI SEKOLAH DASAR - Rajendra, I Made (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
Learning Hindu Religious Education at the elementary school level presents its own challenges compared to learning at the secondary school level. Differences in student characteristics, especially in terms of cognitive, affective, and psychomotor development, require teachers to use learning methods that suit the needs and abilities of students. One method that is considered relevant is the Dharma Carita method, which is based on Dharma Carita that contain moral and spiritual values. This study aims to exploratively analyze the use of the Dharma Carita method in an effort to improve the quality of Hindu Religious Education learning in elementary schools. The method used in this research is a literature study or literature review, which involves a critical review of the academic literature relevant to the topic. The study reviewed existing ideas, findings and knowledge related to the implementation of the Dharma Carita method in the context of religious education in primary schools. The results show that the Dharma Carita method has great potential in shaping students' character and spirituality. Through Dharma Carita , students can learn about important moral values, such as truth, honesty and responsibility. This method is considered effective in conveying moral messages in an interesting and easy-to-understand manner for elementary school students, thus making it the right choice to be used in the classroom.